A novel fluorescent probe for the detection of sulfur dioxide derivatives and its application in biological imaging. (8th September 2021) - Yang, Qing-Qing; Tian, Qin-Qin; Ji, Nan; Duan, Xiao-Hong; Zhu, Xiao-Hong; Zhang, Yan-Li; He, Wei
Abstract : A new probe CA-SO2 to efficiently and specifically detect SO2 was designed. The probe showed a fast response time (<50 s), low detection limit (LOD = 75 nM), large Stokes shift (129 nm) and was applied to detect SO2 in living cells and zebrafish. Abstract : An abnormal level of SO2 is closely related to many diseases. Therefore, developing an effective method for the detection of SO2 in biological environments has important physiological and pathological significance. In this work, a new fluorescent probe (CA-SO2 ) was designed and synthesized for efficiently and specifically detecting SO2 derivatives through nucleophilic addition reaction. The novel fluorescent probe (CA-SO2 ) showed high selectivity, fast response time (within 50 s), and low detection limit (LOD = 75 nM). Furthermore, after adding SO2 derivatives to the probe solution, the color of the solution changes from orange to colorless, which allows "naked eye" detection for SO2 . Moreover, the probe has a large Stokes shift (129 nm) and excellent biocompatibility. The probe has been successfully applied to the detection of SO2 derivatives in living cells and zebrafish.